TINJAUAN PERLINDUNGAN HUKUM BAGI KESETARAAN PENYANDANG DISABILITAS: Review of Legal Protection for Equality of Persons with Disabilities - Moh. Prajamuda Sudirman (PESOLAH: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Equality for people with disabilities is one of the main goals in realizing social justice. Legal protection provided to people with disabilities is an important element in ensuring that their rights are fulfilled without discrimination. This study aims to review aspects of legal protection for people with disabilities using a literature study approach. Through the analysis of legal documents and policies, it was found that various regulations have been formulated to guarantee the rights of people with disabilities, including in the fields of education, employment, health, and general accessibility. However, the implementation of these regulations often encounters challenges, such as low public understanding, lack of supporting facilities, and weak supervision of policy implementation. In an effort to create equality, synergy is needed between the government, society, and the private sector to ensure that existing policies are actually implemented. This includes providing physical, technological, and communication accessibility, as well as strengthening regulations that provide strict sanctions against perpetrators of discrimination. This study also highlights the importance of inclusive education and training for the community to increase awareness and sensitivity to disability issues. With a comprehensive and inclusive approach, it is hoped that the rights of people with disabilities can be better guaranteed, so that an equal and just society is created. Legal protection is an important foundation, but optimal and sustainable implementation efforts are the main key to realizing equality for people with disabilities.